The Public Relations Strategy of the Bogor City DPRD Secretariat in Disseminating Public Information Through Instagram Social Media - Sirait, Kerenhapukh Eunike Befalya; Sartika, Ika (IJESS International Journal of Education and Social Science, 2025)
This study aims to examine the communication strategies implemented by the Public Relations Division of the Bogor City DPRD Secretariat in utilizing Instagram as a primary medium for disseminating public information. In addition, the research focuses on identifying the most effective types of content to be published in order to build a positive institutional image and enhance public participation. The research method employed is qualitative descriptive, with data collection techniques including in-depth interviews, direct observation, and documentation. The findings indicate that the management of the @setwankotabogor Instagram account is conducted professionally, with clear division of tasks among team members, intensive coordination, and a systematic content curation process. The variety of content published includes documentation of DPRD activities, educational content, collaborations, interactive posts, creative visuals, and internal secretariat activities. The use of Instagram has proven effective in delivering information quickly, attractively, and transparently, as well as in fostering active public engagement. Despite facing technical and budgetary limitations, the digital strategies applied have succeeded in positioning Instagram as a modern and accountable public communication platform. This study recommends strengthening human resources and exploring other digital platforms to further support the effectiveness of legislative communication in the future.